Wind of change: Small-scale electricity production and distribution-grid efficiency in Sweden. (April 2021) - Vesterberg, Mattias; Zhou, Wenchao; Lundgren, Tommy
Abstract: In this paper, we measure the technical efficiency for local electricity distribution firms in Sweden, and in particular how small and micro-scale generation affects efficiency scores. Using a two-stage data envelopment analysis to model the technical efficiency and a double bootstrap approach to estimate the determinants of inefficiencies, we show that firms are heterogeneous in terms of inefficiency, but that a large share of small and micro-scale generation is not associated with more inefficient operations. Highlights: We estimate determinants of firm efficiency. A double bootstrap approach is used. We find large heterogeneity in efficiency. We find no decrease in efficiency from micro generation.